Pengaruh EPS, ROA, BOPO terhadap Harga Saham Pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2021-2025 - Erinta Adha Puspita; Sigit Puji Winarko; Andy Kurniawan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This research is motivated by the importance of financial performance information as a basis for consideration for investors in making investment decisions, as well as the ongoing discrepancies in the results of previous studies regarding the effect of financial ratios on stock prices. This study aims to analyze the effect of Earning Per Share (EPS), Return on Assets (ROA), and Operating Expenses to Operating Income (BOPO) on the stock prices of banking companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2025 period. This study employs a quantitative approach with a causality method. The population consists of banking companies listed on the Indonesia Stock Exchange for the 2021–2025 period. The sample was determined using a purposive sampling technique, resulting in 17 companies with a total of 85 observations. The data used are secondary data obtained from the companies' annual financial reports and analyzed using multiple linear regression analysis with the assistance of the SPSS program. Prior to hypothesis testing, the data underwent classical assumption tests, which included normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results indicate that, partially, Earning Per Share (EPS) has no significant effect on stock prices, Return on Assets (ROA) has no significant effect on stock prices, while Operating Expenses to Operating Income (BOPO) has a significant effect on stock prices. Simultaneously, EPS, ROA, and BOPO significantly affect the stock prices of banking companies listed on the Indonesia Stock Exchange for the 2021–2025 period. The findings indicate that information regarding earnings per share and company operational efficiency are factors considered by investors in determining investment decisions, whereas the level of profitability measured by ROA has not been able to exert a significant influence on stock price movements during the research period. This research is expected to serve as a reference for investors, companies, and future researchers in understanding the factors influencing stock prices in the banking sector.